Evaluation of Suzor forceps training by studying obstetric anal sphincter injuries: a retrospective study - Perrine COSTE MAZEAU; Nedjma BOUKEFFA; Nathalie TICAUD BOILEAU; Samantha HUET; Maud TRAVERSE; Jean-Luc EYRAUD; Alexine LAGUERRE; Cyrille CATALAN; Cécilia RIEDL (BMC, 2020)
Abstract Background Instrumental deliveries are an unavoidable part of obstetric practice. Dedicated training is needed for each instrument. To identify when a trainee resident can be entrusted with instrumental deliveries by Suzor forceps by studying obstetric anal sphincter injuries. Methods A French retrospective observational study of obstetric anal sphincter injuries due to Suzor forceps deliveries performed by trainee residents was conducted from November 2008 to November 2016 at Limoges University Hospital. Perineal lesion risk factors were studied. Sequential use of a vacuum extractor and then forceps was also analyzed. Results Twenty-one residents performed 1530 instrumental deliveries, which included 1164 (76.1%) using forceps and 89 (5.8%) with sequential use of a vacuum extractor and then forceps. Third and fourth degree perineal tears were diagnosed in 82 patients (6.5%). Residents caused fewer obstetric anal sphincter injuries after 23.82 (+/− 0.8) deliveries by forceps (p = 0.0041), or after 2.36 (+/− 0.7) semesters of obstetrical experience (p = 0.0007). No obese patient (body mass index> 30) presented obstetric anal sphincter injuries (p = 0.0013). There were significantly fewer obstetric anal sphincter injuries after performance of episiotomy (p <  0.0001), and more lesions in the case of the occipito-sacral position (p = 0.028). Analysis of sequential instrumentation did not find any additional associated risk. Conclusion Training in the use of Suzor forceps requires extended mentoring in order to reduce obstetric anal sphincter injuries. A stable level of competence was found after the execution of at least 24 forceps deliveries or after 3 semesters (18 months) of obstetrical experience.